1989
DOI: 10.1079/bjn19890127
|View full text |Cite
|
Sign up to set email alerts
|

Particle breakdown and rumen digestion of fresh ryegrass (Lolium perenne L.) and lucerne (Medicago sativa L.) fed to cows during a restricted feeding period

Abstract: 1. Five rumen-fistulated cows were given freshly cut ryegrass (Lolium perenne L.) and lucerne (Medicago sotiva 2. Cattle were required to consume their daily allowance (offered ad lib.) in two 2 h feeding periods daily.3. During the first 2 h feeding period, dry matter (DM) intakes of ryegrass (4.75 kg) and lucerne (4.85 kg) were similar. Eating reduced 46% of ryegrass and 61 % of lucerne to a size able to pass a 2 mm sieve (P < 0.001). Rumen DM particles retained on the 2 and 4 mm sieves had a low probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 15 publications
4
59
0
4
Order By: Relevance
“…In this context, it was emphasized that the effect of fi lling up the rumen of animals fed on leguminous plants is lower due to the weakness of the particle (VAGHORN et al, 1989) and to the short retention time (HOFFMAN et al, 1998) compared to grass plants.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, it was emphasized that the effect of fi lling up the rumen of animals fed on leguminous plants is lower due to the weakness of the particle (VAGHORN et al, 1989) and to the short retention time (HOFFMAN et al, 1998) compared to grass plants.…”
Section: Resultsmentioning
confidence: 99%
“…Trials in agricultural science results indicated that legumes are less costly to diminish in particle size than grasses when tested mechanically (Paul and Mika 1981;unpublished data in Wilson and Kennedy 1996;Henry et al 1997;Wilman et al 1997) or in vivo by the mastication action of domestic ruminants (Moseley and Jones 1984;Waghorn et al 1989;Wilman et al 1997). This is also reflected in the longer time spent ruminating (per unit of forage intake) for grass as compared with legumes in domestic ruminants (Sudweeks et al 1981;Wilman et al 1997;data in Coleman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This supports the classical concept of Van Soest (1982) that plant cell walls would limit rumen filling, so that animals would regulate their intake at a relatively constant NDF intake level. While the lower level of NDF of legumes, compared to grasses, can explain the increase in DMI (Figure 2a), the observed positive associative effect seems to be, instead, due to fast digestion of the soluble fraction of legumes, a higher rate of particle breakdown (Moseley and Jones, 1984;Waghorn et al, 1989) and, finally, a higher passage rate through the rumen. Dewhurst et al (2003) suggested that the high intake level of legume silages may be the result of different mechanisms: high rates of particle breakdown with lucerne, and high rates of fermentation and passage with white clover.…”
Section: Associative Effects Between Temperate Grasses and Legumesmentioning
confidence: 90%